KONTRIBUSI PT. MUTIARA ADONARA TERHADAP PENYERAPAN TENAGA KERJA DAN PENDAPATAN KELUARGA DI DESA OYANGBARANG KECAMATAN WOTAN ULUMADO KABUPATEN FLORES TIMUR - Felix Mubera Sogen; Marthen R Pellokila; Marselina Ratu (RJABM (Research Journal of Accounting and Business Management), 2023)
Felix Mubera Sogen, Marthen R. Pellokila, Marselina Ratu Program Studi Ekonomi Pembangunan Fakultas Ekonomi Dan Bisnis Universitas Nusa Cendana Email: felix.m.sogen@gmail.com ABSTRACT This research was conducted with the aim of explaining the contribution of PT. Mutiara Adonara on employment absorption in Oyangbarang Village, Wotan Ulumado District, East Flores Regency and explained the contribution of PT. Mutiara Adonara on the income of the family of company workers in Oyangbarang Village. This research is a descriptive research with a qualitative approach, the type of data used is qualitative and quantitative data with primary and secondary data sources. The research location of PT. Mutiara Adonara which is located in Oyangbarang Village, Wotan Ulumado District, East Flores Regency, the collection technique uses observation, interviews and documentation with data analysis techniques consisting of data reduction, data presentation and drawing conclusions. The results of this study show the contribution of PT. Mutiara Adonara on employment absorption in Oyangbarang Village by 35%, the contribution of PT. Mutiara Adonara on employment absorption in the Wotan Ulumado District of 3.53% and the contribution of PT. Mutiara Adonara on employment absorption in East Flores Regency by 0.12%. With these results based on the environmental quality scale the contribution of PT. Mutiara Adonara regarding employment in Oyangbarang Village is in the low category and for Wotan Ulumado District and East Flores Regency it is still in the very low category. While the contribution of PT. Mutiara Adonara to the income of the families of company workers in Oyangbarang Village, Wotan Ulumado District, East Flores Regency, amounting to 89.02%. This can be interpreted that, the income from working at PT. Mutiara Adonara has a large contribution to family labor income. Keywords: Contribution of PT. Mutiara Adonara, Labor Absorption, Family Income.